Development of functionally graded composite for fabrication of dental post / Ahmed Abdullah Ali Madfa - Ali Madfa, Ahmed Abdullah (2011)
Introduction: Ideally, dental posts should have varying stiffness along its length, where the coronal end require higher stiffness for better retention and rigidity of the core, and this stiffness should reduced towards the apical end. The purpose of this study is to develop a novel dental post that would meet this requirement. Objectives: This multi-staged study aimed to fabricating, characterizing and optimizing three novel formulation of functionally graded multilayered composites (FGMC) for possible applications as dental post. Three functionally graded dental posts (FGSPs) derived from optimised FGMC were later evaluated for thermo-mechanical stress and stress distribution when used as dental post in modelled endodontically treated human maxillary incisor. Finally, fracture resistance and failure modes of endodontically treated bovine incisors restored with three FGSPs prototypes were compared to those restored with titanium and cast posts. Methods: FGMC were fabricated using pressureless sintering and hot isostatic press. SEM, EDX and XRD techniques were used for microstructural and compositional characterization followed by evaluation of selected physical and mechanical properties. The thermo-mechanical stress under hot and cold conditions was conducted using finite element analysis (FEA). FEA was also used to investigate the stress and strain distributions within the tooth-model, along the centre of the post and at the interface of post and surrounding structures when loaded (100 N) in vertical, oblique, and horizontal directions. Three FGSPs prototypes of different compositions; ZrO2-Ti-HA, Al2O3-Ti-HA and Ti-HA were fabricated and used to restore 30 endodontically treated bovine incisors. Fracture resistance and failure modes were evaluated and compared against teeth restored with titanium and cast posts. Sound extracted teeth and endodontically treated teeth without post serves as the control groups. Results: SEM, EDX and XRD analyses from different areas of the FGMC confirmed the presence and gradual change of Ti-HA-ZrO2-Al2O3 elements and phases. The physical and mechanical properties also changed gradually according to the composition of each layer confirming that the graded multilayered composites structure was functional. It was evident that the FGSP models returned to near body temperature faster than zirconia and titanium posts within the stipulated time frame of 5 seconds. The magnitude of thermal stresses at the post and surrounding structures interface were greater in the zirconia and titanium posts especially at the middle third of the posts. The maximum von Mises, compressive and tensile stresses and strains were mainly concentrated at the tooth periphery while shear stress distributions were primarily located at the post/dentine interface. Lower von Mises, compressive, tensile and shear stresses were observed for FGSP models. There is no significant difference in mean fracture resistance between cast (1398.58N±314.29), titanium (1408.65 N ± 226.39) and FGSPs (ZrO2-HA-Ti, 1299.31N ± 251.74; Al2O3-HA-Ti, 1242.53N± 196.55 and Ti-HA-Ti, 1267.68N±173.00). However, cast, titanium and FGSP posts showed significantly higher fracture resistance compared to the control groups. For failure mode, FGSPs and endodontically treated teeth only showed higher percentage of repairable failures compared to titanium, cast posts and sound extracted teeth. Conclusions: FGMC was successfully optimised and three FGSPs prototypes were fabricated. FEA showed that zirconia and titanium posts produced higher thermal stresses than FGSPs. FGSPs also showed lower von Mises, compressive, tensile and shear stresses compared to zirconia and titanium posts. There was no significant difference in the mean fracture resistance amongst FGSPs, titanium and cast posts. Teeth restored using titanium and cast posts resulted in higher number of non repairable fractures whilst FGSPs and endodontically treated only groups exhibited higher number of repairable fractures.